Trends And Opportunities In Fun Science Learning For Early Childhood: A Bibliometric Analysis (2014–2023) - Noor, Faiq Makhdum (THUFULA, 2024)
Research on science learning for early childhood has increased from year to year. Science learning is important during early childhood because it is an important period for laying the foundation for developing children's various potentials and characters. This research aims to analyze research trends in fun science learning for early childhood, visualize existing research trends, and find novelty opportunities for future research based on analysis of research themes that have been carried out so far. This research uses bibliometric techniques using the Scopus database which was conducted on September 27 2024 with the keywords "fun science learning for early childhood". Data files from the Scopus database are downloaded in .csv and .ris formats and visualized using the VOSViewer application. The analysis was carried out over the last ten years starting from 2014 to 2023 with a total of 4.204 documents. Based on the results of the analysis, it was found that the research trend regarding science learning for early childhood has increased from year to year, apart from that there are also four clusters in the VOSViewer visualization, and opportunities for novelty can be seen from several keywords that look small, not dominant, and not has a relationship with other words in the VOSViewer visualization. Novelty opportunities can be found in keywords including children development, childhood education, science learning, early childhood teacher, playful learning, pedagogical practice, early childhood education, and preschooler